DEVELOPING THE SPIRIT OF STUDENTS 'ENTREPRENEURS IN THE BORDER AREA IN UTILIZING OIL WASTE FOR BIODIESEL FUELS DISTRICT BENGKAYANG-KALBAR - -, Usman; Kristianto, Aloysius Hari (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Left behind Territory requires a high entrepreneurial spirit of its inhabitants. This is understood because in the area the builder is still left behind so that the field of work is very limited. To that end, research on the entrepreneurial spirit among young people who become a local development expectations important. Other than that thing was, it needed research into the field of entrepreneurship that is appropriate considering the limited facilities and resources available. Cooking oil is a processing tool foodstuffs commonly in use by the mother-housewife in general. Usually cooking oils used as ingredients in the household needs for the management of food ingredients. As for cooking oil (Cooking oil waste) or waste cooking oil is cooking oil that is used repeatedly restarted. Used cooking oil repetitive very harmful to human health; because its repeated use with high temperatures will result in free fat content. Effect of free fat is the emergence of various diseases such as liver cancer and others. Given the effects of negative, cooking oil can not be consumed again. waste cooking oil turned out to be an alternative fuel, substitute diesel.Solar diesel fuel is one of the more time will step because the raw material comes from fossils that notes bene including resources that can not be renewed.Therefore, processing cooking oil as a substitute for fuel, this is an exciting and necessary thing to experience. In terms of the benefits of jelantah oil is very good to create new business opportunities that is as a raw material biosdiesel environmentally friendly and with the concept of sustainable development (sustainebel development) in addition to the cooking oil processing is also seen to be one effort to deepen the entrepreneurship spirit of students STIM Shanti Bhuana.In relevance with the border area which at the same time left behind.Jelantah cooking oil is also expected to create new jobs and increase the income of the community. Not only that waste cooking oil cooking oil into fuel is expected to be a systematic and structured solution to the problem low people's opinions. At the same time providing an understanding for the local community about the adverse health effects of using repeated cooking  oil.Keywords: Entrepreneurship, Waste of cooking oil, Biodiesel.